Perspective—Insights into Solar-Rechargeable Redox Flow Cell Design: A Practical Perspective for Lab-Scale Experiments. Issue 12 (10th December 2021) - Whitley, Shaun; Bae, Dowon
Abstract : Solar-rechargeable redox flow batteries (SRFBs) offer feasible solar energy storage with high flexibility in redox couples and storage capacity. Unlike traditional redox flow batteries, homemade flow cell reactors are commonly used in most solar-rechargeable redox flow batteries integrated with photoelectrochemical devices as it provides high system flexibility. This perspective article discusses current trends of the architectural and material characteristics of state-of-the-art photoelectrochemical flow cells for SRFB applications. Key design aspects and guidelines to build a photoelectrochemical flow cell, considering practical operating conditions, are proposed in this perspective.